Effect of Iron Loading on Quiescent Crystallization of Syndiotactic Polypropylene/Iron Composites - Ahmad, Naveed (Engineering, Technology & Applied Science Research, 2025)
The present study investigates the crystallization kinetics of the syndiotactic polypropylene/iron (sPP/Fe) composites using the rheological and Differential Scanning Calorimetry (DSC) techniques to evaluate the impact of varying iron content. Rheology, which is particularly sensitive under slow crystallization kinetics, was employed to complement the widely used DSC method. The current study aimed to integrate the aforementioned approaches to provide a comprehensive understanding of how the iron content influences the crystallization behavior of the sPP composites. Non-isothermal and isothermal crystallization experiments revealed that the increasing iron content significantly enhanced the crystallization and melting temperatures, indicating improved thermal stability and crystallinity. The rheological measurements, carried out using an Atomic Rheometric Expansion System (ARES), demonstrated higher sensitivity than the DSC at low iron concentrations, providing a more precise detection of crystallization kinetics. The results showed excellent agreement between the two techniques, confirming the robustness of rheology as a complementary method. This study underscores the importance of the iron content in tailoring the thermal and mechanical properties of sPP composites and highlights the value of integrating rheological methods with traditional thermal analysis for polymer characterization.